An Approach to Determine the Average Transport Delays at Adjacent Territory Exit on the Highway - Ye. V. ,; Bieletska, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2022)
The main distinguishing features of methods to determine transport delays at unsignalized intersections with unequal directions, which are quite similar to adjacent territory exit to arterial streets and roads of large, significant and most significant cities by the principles of organization and regulation of traffic, are analyzed and determined. The purpose of the article is to develop analytical models to determine transport delays at adjacent territory exit to arterial streets and roads. The object of the study is the interaction of traffic flow moving through the urban highway network and the flow of vehicles leaving adjacent territory. The study proposes an approach to determine transport delays at adjacent territory exit to arterial streets and roads, which is based on the principles of a queuing theory and takes into account the priority of traffic in competing directions. As the main information base for the use of proposed approach to determine transport delays at adjacent territory exit, it is necessary to have the value of the traffic flow intensity in competing directions and the passing time of the vehicle dynamic dimensions, which can be obtained by conducting field observations at the selected experimental research objects. The developed approach needs to be experimentally verified by comparing empirical and theoretical results of calculating transport delays at adjacent territory exit to the arterial network, as well as by conducting a simulation experiment on selected of experimental research objects. The proposed analytical models to determine the average transport delays simplify the perception of traffic flows interaction at adjacent territory exit.